Corporate restructuring and export performance in the transition process: The case of Eastern Germany - Klaus-Dieter Schmidt (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
Economic restructuring in the transition from plan to market concerns the way enterprises try to achieve competitive advantage. Therefore, enterprises have to decide where to compete, that is to say with which product they should enter which markets, and how to compete, that is by which strategy they could succeed. During the seven years since unification, the eastern German economy has undergone considerable structural changes. However, the outcome is a poor market specialization: industries which sell their products mainly in local markets have remarkably increased their share in total output, while industries producing for world-wide markets have lost importance. Sailing into the safe harbour of local markets may be the need of the moment for many companies. But it is a dangerous strategy. In the long run, it may prove to be a trap without any escape. The paper provides a selective and interpretative account of the restructuring process in eastern German manufacturing. It starts with the given constraints - exchange rate and wage convergence - which constitute the wrong model for opening up a closed economy. It presents some stylized facts revealing a strong vertical differentiation between eastern and western German producers - with respect to product quality and product markets as well as with respect to technological and organizational environment. As a result, the division of labour between the eastern German economy and the rest of the world tends to be an inter-industry type rather than an intra-industry one. Finally, the paper turns to the key policy question of how to overcome these difficulties. It scrutinizes the main arguments for and against government's trade promotion towards eastern German enterprises.
Keywords: P52; 330; Industrieller Strukturwandel; Nicht-handelbares Gut; Exportindustrie; Internationaler Wettbewerb; Außenhandelsförderung; Neue Bundesländer